(untitled) (Research, Society and Development, 2022)
This work presents an experience report on the teaching process of Chemistry through the use of Project Based Learning (ABPr) as Active Learning Methodology (MAA). The methodology consisted of encouraging autonomy and capacity to absorb content in a participatory manner by students belonging to the first period of a Higher Education Course located in a Federal Institution in the South of Minas Gerais. To carry out the projects during Emergency Remote Teaching (ERE), students were divided into teams guided by the teacher. Then, the projects were presented in the synchronous class, with the relevant points being discussed, as well as suggestions for improvement for their continuity. Three projects were selected: Agrochemistry in focus, Isolation by dielectric oil and Quiz Chemistry. The results revealed that the methodology used made it easier to understand the contents that may be related to daily life, and the reports of the students involved indicated positive aspects related to interaction and critical development regarding the issues addressed. Thus, it can be inferred that the ABPr allowed a formative assessment of students, so that the curricular contents were worked taking into account significant learning.